Still not out of the woods? New Jersey schools during the recession and beyond - Rajashri Chakrabarti; Max Livingston (Federal Reserve Bank of New York, 2013)
Schools are essential in forming human capital and in improving the long-term health of the economy. They are also heavily reliant on state and local funds, which were severely depleted during the Great Recession. To alleviate some of the strain on local budgets, the federal government passed and implemented a large stimulus package, which included funds for school districts. However, the stimulus funds were drawn down beginning in 2011, at a time when state and local revenues were still under pressure. In this paper, we use a detailed panel data set of all school districts in New Jersey for the period 1999 through 2012 and analyze the impact of this series of events on New Jersey school finances using a trend-shift analysis. We find that the recession led to cuts in funding and expenditure. While the stimulus served as an effective stopgap against major cuts, the picture was very different once the stimulus funds were depleted, with significantly deeper cuts in both funding and spending. With cutbacks in state aid and the withdrawal of the stimulus funding, local funding played a larger role, despite the fact that local funding was also decreasing relative to trend. Examining the components of expenditure, we find that instructional categories were prioritized over noninstructional, so instructional expenditure only sustained small cuts in the initial years after recession. But when the stimulus dried up and the economy was still stagnating, instructional expenditure received severe cuts. We analyze variations by metropolitan area, and find that Camden experienced the largest cuts while Wayne experienced the smallest (although the declines in funding and expenditure were still significant). Our findings are an important step in understanding how recessions and fiscal policy affect school finances and inform future policy decisions relating to school finances during fiscal crises.
Keywords: H40; I20; R10; R51; 330; school finance; recession; ARRA; federal stimulus